Reaching Absent and Refusing Individuals During Home-Based HIV Testing Through Self-Testing—at What Cost? - Amstutz, Alain; Matsela, Lineo; Lejone, Thabo Ishmael; Kopo, Mathebe; Glass, Tracy Renée; Labhardt, Niklaus Daniel (Frontiers in Medicine, 2021)
Introduction In the HOSENG trial (NCT03598686), secondary distribution of oral self-tests for persons absent or refusing to test during a home-based HIV testing campaign in rural Lesotho resulted in an increase in testing coverage of 21% compared to a testing campaign without secondary distribution. This study aims to determine the per patient costs of both HOSENG trial arms. Method We conducted a micro-costing study to estimate the cost of home-based HIV testing with and without secondary self-test distribution from a provider’s perspective. A mixture of top-down and bottom-up costing was used. We estimated both the financial and economic per patient costs of each possible testing scenario. Costs were adjusted to 2018 US. Results The overall provider cost for delivering the home-based HIV testing with secondary distribution was US36'481 among the 4174 persons enumerated and 3094 eligible for testing in the intervention villages, compared to US28'620 for 3642 persons enumerated and 2727 eligible for testing in control. The cost per person eligible for testing was US11.79 in intervention versus US10.50 in control. This difference was mainly driven by the cost of distributed oral self-tests. The cost per person tested was, however, lower in intervention villages (US15.70 vs US22.15) due to the higher testing coverage achieved through self-test distribution. Cost per person confirmed new HIV+ was US889.79 in intervention and US753.17 in control. Conclusion During home-based HIV testing in Lesotho, secondary distribution of self-tests for persons absent or refusing to test during the visit reduced costs per person tested.